Constraining activity and growth substrate of fungal decomposers via assimilation patterns of inorganic carbon and water into lipid biomarkers - Jabinski, Stanislav; D M Rangel, Wesley; Kopáček, Marek; Jílková, Veronika; Jansa, Jan; Meador, Travis B (Applied and environmental microbiology, 2024)
Fungi are among the few organisms on the planet that can metabolize recalcitrant carbon (C) but are also known to access recently produced plant photosynthate. Therefore, improved quantification of growth and substrate utilization by different fungal ecotypes will help to define the rates and controls of fungal production, the cycling of soil organic matter, and thus the C storage and CO2 buffering capacity in soil ecosystems. This pure-culture study of fungal isolates combined a dual stable isotope probing (SIP) approach, together with rapid analysis by tandem pyrolysis-gas chromatography-isotope ratio mass spectrometry to determine the patterns of water-derived hydrogen (H) and inorganic C assimilated into lipid biomarkers of heterotrophic fungi as a function of C substrate. The water H assimilation factor (αW) and the inorganic C assimilation into C18:2 fatty acid isolated from five fungal species growing on glucose was lower (0.62% ± 0.01% and 4.7% ± 1.6%, respectively) than for species grown on glutamic acid (0.90% ± 0.02% and 7.4% ± 3.7%, respectively). Furthermore, the assimilation ratio (RIC/αW) for growth on glucose and glutamic acid can distinguish between these two metabolic modes. This dual-SIP assay thus delivers estimates of fungal activity and may help to delineate the predominant substrates that are respired among a matrix of compounds found in natural environments.IMPORTANCEFungal decomposers play important roles in food webs and nutrient cycling because they can feed on both labile and more recalcitrant forms of carbon. This study developed and applied a dual stable isotope assay (13C-dissolved inorganic carbon/2H) to improve the investigation of fungal activity in the environment. By determining the incorporation patterns of hydrogen and carbon into fungal lipids, this assay delivers estimates of fungal activity and the different metabolic pathways that they employ in ecological and environmental systems.
Keywords: Glucose; vodík; Hydrogen; Ecosystem; mastné kyseliny; voda; uhlík; Bacteria; glukosa; Fatty Acids; Soil; izotopy uhlíku; Glutamic Acid; water hydrogen assimilation factor; dissolved inorganic carbon (DIC); Carbon; Carbon Isotopes; dual stable isotope probing; ekosystém; fungal membrane lipids; pyrolysis-gas-chromatography; půda; heterotrophic CO2 assimilation; kyselina glutamová; Water